1996
DOI: 10.1016/s0092-8674(00)81337-9
|View full text |Cite
|
Sign up to set email alerts
|

UNC-40, a C. elegans Homolog of DCC (Deleted in Colorectal Cancer), Is Required in Motile Cells Responding to UNC-6 Netrin Cues

Abstract: UNC-6 netrin, a laminin-related protein secreted from neuroglia and neurons along the ventral midline, orients migrating cells and pioneering growth cones on the nematode epidermis. UNC-5, a cell surface protein expressed on motile cells and pioneer axons, orients movements away from UNC-6 sources. UNC-40, a homolog of the cell surface proteins DCC (Deleted in Colorectal Cancer) and neogenin, is also expressed on motile cells and pioneer neurons. UNC-40 acts cell autonomously to orient movement toward UNC-6 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
301
0
4

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(320 citation statements)
references
References 36 publications
9
301
0
4
Order By: Relevance
“…So far, no homotypic interaction of DCC has been con®rmed. However, it has been shown that DCC is a candidate component of the receptor for netrin-1 (Keino-Masu et al, 1996;Chan et al, 1996;Kolodziej et al, 1996). Therefore, we also evaluated whether netrin-1 can stimulate or inhibit DCC-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…So far, no homotypic interaction of DCC has been con®rmed. However, it has been shown that DCC is a candidate component of the receptor for netrin-1 (Keino-Masu et al, 1996;Chan et al, 1996;Kolodziej et al, 1996). Therefore, we also evaluated whether netrin-1 can stimulate or inhibit DCC-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…The receptors for the netrins are 16,17 ) and in C. elegans, and their corresponding mammalian homologs are DCC (deleted in colorectal cancer), neogenin 19,20 and UNC5A-D (also known as . DCC/ UNC-40 seems to be required for both the attractive and repulsive responses, whereas UNC-5 is required only for repulsion [17][18][19][20]25,26 .…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…[21][22][23][24]. DCC/ UNC-40 seems to be required for both the attractive and repulsive responses, whereas UNC-5 is required only for repulsion [17][18][19][20]25,26 . Heterodimerization of UNC-40 with UNC-5 may convert UNC-40 from mediating attraction to repulsion 27 .…”
mentioning
confidence: 99%
“…Genetic analyses have now established that interactions between the products of three genes, unc-5, unc-6, and unc-40, regulate the circumferential guidance of growth cones/axons (and the migration of cells) along the C. elegans body wall (for reviews see Culotti and Kolodkin, 1996;Hedgecock and Norris, 1997;Culotti and Merz, 1998;Branda and Stern, 1999;Merz and Culotti, 2000). More specifically, the vertebrate Netrin ortholog, UNC-6, is required for both dorsal and ventral guidance events (Hedgecock et al, 1990;Ishii et al, 1992;Wadsworth et al, 1996), the vertebrate DCC ortholog, UNC-40, is required for ventral (and to a lesser extent dorsal) guidance events (Hedgecock et al, 1990;Chan et al, 1996), and a novel Ig-superfamily member, UNC-5, is required exclusively for dorsally-directed axon guidance (LeungHagesteijn et al, 1992;Hamelin et al, 1993). Furthermore, UNC-40 and UNC-5 are each capable of acting cell autonomously to orient growth cones either towards or away, respectively, from sources of UNC-6 (see Culotti and Kolodkin, 1996;Hedgecock and Norris, 1997;Merz and Culotti, 2000 and references therein).…”
Section: Elegans Body Wallmentioning
confidence: 99%